PEMBERDAYAAN PEREMPUAN DALAM PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT (PNPM) MANDIRI PERKOTAAN DI KOMUNITAS RAJUT ERWELA - Salsabila, Zakiah; Kismartini, Kismartini (Journal of Public Policy and Management Review, 2025)
Development so far has been carried out more about infrastructure and urban planning, rarely talking about human development so that the poor continue to be squeezed and cannot get out of the circle of poverty. Poverty alleviation carried out by the government always places the poor as objects, namely by providing cash or non-cash assistance so that they continue to depend on this assistance. The poor as subjects means that they can participate in solving their own problems through empowerment which will later achieve independence. Women are often underestimated by society so that they continue to be marginalized. Therefore, women's empowerment is now widely pursued because empowered women are able to take part in increasing family income. The purpose of this study is to analyze the process of empowering women in the Komunitas rajut Erwela in Lenteng Agung Village, South Jakarta and to analyze the supporting and inhibiting factors for women's empowerment in the Komunitas Rajut Erwela, Lenteng Agung Village, South Jakarta. This research uses a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. The results of this study indicate that the empowerment process in the Komunitas Rajut Erwela has been successful in increasing the capacity and independence of women because it is supported by high motivational factors from community members. The inhibiting factors are government policies that have not provided support for the implementation of empowerment, limited budget and capital, and incomplete facilities and infrastructure.